2013
DOI: 10.1111/ijpp.12039
|View full text |Cite
|
Sign up to set email alerts
|

Description and process evaluation of pharmacists’ interventions in a pharmacist-led information technology-enabled multicentre cluster randomised controlled trial for reducing medication errors in general practice (PINCER trial)

Abstract: ObjectiveTo undertake a process evaluation of pharmacists' recommendations arising in the context of a complex IT-enabled pharmacist-delivered randomised controlled trial (PINCER trial) to reduce the risk of hazardous medicines management in general practices.MethodsPINCER pharmacists manually recorded patients' demographics, details of interventions recommended, actions undertaken by practice staff and time taken to manage individual cases of hazardous medicines management. Data were coded, double-entered int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 17 publications
0
7
0
1
Order By: Relevance
“…Forty-three studies were noninterventional (Table 1), and 13 included an intervention (Table 2). [59][60][61][62][63][64][65][66][67][68][69][70][71] The noninterventional studies that measured potentially inappropriate prescribing/ medications (PIPs) were all judged to be of low risk of bias because they included defined patient populations with clear process measure outcomes (whether or not a Beers list medication was on a patient's medication list, eg). The risk of bias assessment of noninterventional studies that measured ADEs or drug-related problems (DRPs) is shown in Supplementary Table 3.…”
Section: Resultsmentioning
confidence: 99%
“…Forty-three studies were noninterventional (Table 1), and 13 included an intervention (Table 2). [59][60][61][62][63][64][65][66][67][68][69][70][71] The noninterventional studies that measured potentially inappropriate prescribing/ medications (PIPs) were all judged to be of low risk of bias because they included defined patient populations with clear process measure outcomes (whether or not a Beers list medication was on a patient's medication list, eg). The risk of bias assessment of noninterventional studies that measured ADEs or drug-related problems (DRPs) is shown in Supplementary Table 3.…”
Section: Resultsmentioning
confidence: 99%
“…The PINCER trial demonstrated the clinical and cost‐effectiveness of pharmacist‐delivered medication reviews in primary care in the United Kingdom, 40 and their process evaluation showed that GPs acted on pharmacist recommendations the majority of times (61%), 41 compared with SPPiRE GPs who acted on self‐identified PIP 55% of the time. It may be that collaboration with a colleague facilitates making medication changes and a medicines management multimorbidity intervention that adopts this approach, 42 has recently been piloted in Irish primary care 43 .…”
Section: Discussionmentioning
confidence: 99%
“…This study is one of a growing number of process evaluations published independently of the main RCT findings [ 15 , 47 , 48 ] and is one of first to adopt a process evaluation framework explicitly intended for use in cluster RCTs [ 19 ]. Quantitative and qualitative data were systematically collected and rigorously analysed, providing an insight into patient and GP perspectives of the intervention and its implementation.…”
Section: Discussionmentioning
confidence: 99%